2019
DOI: 10.1021/acsanm.9b01143
|View full text |Cite
|
Sign up to set email alerts
|

WS2 Nanopowders as High-Temperature Lubricants: An Experimental and Theoretical Study

Abstract: In view of the high-temperature operation conditions in lubrication, this work focused on the lubrication performances of WS 2 nanopowders at high temperatures. A certainly low coefficient of friction (CoF) (about 0.05) of WS 2 nanopowders is observed at 100− 300 °C. High-temperature tribological experiments are performed, and first-principles simulations are applied to investigate the lubrication performances simultaneously. According to the XRD and XPS spectra, it should be noticed that WS 2 lubricating film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Spurious reactions between WS 2 and interfacing materials and/or atmospheric gases can negatively impact lubricity by forming undesirable compounds, like WO x , or by dissociating WS 2 . 77,78 The XPS results reported here inform superior lubricant design by elucidating the chemistry in relevant metal−WS 2 lubricant systems. For instance, Cr is a common alloying element in steels, which commonly interface with dry lubricants, and the Au−WS 2 system shows promise as a solid lubricant system.…”
Section: ■ Methodsmentioning
confidence: 81%
“…Spurious reactions between WS 2 and interfacing materials and/or atmospheric gases can negatively impact lubricity by forming undesirable compounds, like WO x , or by dissociating WS 2 . 77,78 The XPS results reported here inform superior lubricant design by elucidating the chemistry in relevant metal−WS 2 lubricant systems. For instance, Cr is a common alloying element in steels, which commonly interface with dry lubricants, and the Au−WS 2 system shows promise as a solid lubricant system.…”
Section: ■ Methodsmentioning
confidence: 81%
“…WS 2 nanopowders have also been used in high-temperature applications and achieved a COF of 0.05 in temperatures ranging from 100 to 300 °C. [112] An accompanying theoretical analysis found that the platelets adhered well to a steel substrate and allowed for easy shearing on the (002) plane.…”
Section: Sliding Bearingsmentioning
confidence: 99%
“…In many cases, the use of 2D materials as solid lubricants was especially beneficial for aerospace [110] and high-temperature applications. [63,111,112] Meanwhile, the incorporation of 2D materials as additives found its niche in the automotive industry [113] and for marine applications. [114] We expect that the potential industrial uses for 2D nanomaterials in sliding bearings will continue to increase in the near future when combined with a wide range of materials, such as soft metals (e.g., bronze), polymers (e.g., PA, POM, PTFE), and composites, even if they are not yet represented in published research and are not applied in sliding bearings already in industrial usage.…”
Section: Sliding Bearingsmentioning
confidence: 99%
“…Bulk WS 2 has an indirect band gap of 1.3 eV, while the monolayer has a direct band gap of ∼2 eV . It has shown potential application in photovoltaics, photodetectors, hydrogen evolution reaction (HER), field effect transistors (FETs), gas sensing, biosensing, lubricants, batteries, supercapacitors, and memristors …”
Section: Introductionmentioning
confidence: 99%
“…Bulk WS 2 has an indirect band gap of 1.3 eV, while the monolayer has a direct band gap of ∼2 eV. 3 It has shown potential application in photovoltaics, 4 photodetectors, 5 hydrogen evolution reaction (HER), 6 field effect transistors (FETs), 7 gas sensing, 8 biosensing, 9 lubricants, 10 batteries, 11 supercapacitors, 12 and memristors. 13 One of the major challenges in the development and commercialization of 2D materials is to scale up their growth to a large area with controllable thickness, crystallinity, uniformity, morphology, phase, and crystallite orientation.…”
Section: Introductionmentioning
confidence: 99%